2018
DOI: 10.1002/ajpa.23449
|View full text |Cite
|
Sign up to set email alerts
|

The genetic assimilation in language borrowing inferred from Jing People

Abstract: We conclude that the formation and language change of present-day Jing people have involved genetic assimilation of surrounding East Asian populations. The language borrowing, in this case, is not only a cultural phenomenon but has involved demic diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Previous studies suggested that O2a2b1-M134 (xM117) was one of the predominant paternal lineages in Tibeto-Burman and Sinitic populations, which originated in northern EA and was associated with the millet-farming related Proto-Sino-Tibetan populations (Ning et al, 2016;Wang et al, 2018;Yan et al, 2014). We also observed sub-lineages of haplogroup O1-F265 in the study populations, suggesting the genetic affinity with coastal southern EA ancestry with haplogroup O1a-M119 and O1b1a1a-M95 (Huang et al, 2018;Zhao et al, 2010). Except for the Pumi_N, we found other Yunnan Tibeto-Burman and Austroasiatic populations have haplogroup C-M216 including C1a-CTS11043 and C2c1-F2613, indicating gene flow from north Eurasian steppe populations (Zhong et al, 2010).…”
Section: Paternal and Maternal Haplogroup Genotyping Of Each Individualsupporting
confidence: 61%
“…Previous studies suggested that O2a2b1-M134 (xM117) was one of the predominant paternal lineages in Tibeto-Burman and Sinitic populations, which originated in northern EA and was associated with the millet-farming related Proto-Sino-Tibetan populations (Ning et al, 2016;Wang et al, 2018;Yan et al, 2014). We also observed sub-lineages of haplogroup O1-F265 in the study populations, suggesting the genetic affinity with coastal southern EA ancestry with haplogroup O1a-M119 and O1b1a1a-M95 (Huang et al, 2018;Zhao et al, 2010). Except for the Pumi_N, we found other Yunnan Tibeto-Burman and Austroasiatic populations have haplogroup C-M216 including C1a-CTS11043 and C2c1-F2613, indicating gene flow from north Eurasian steppe populations (Zhong et al, 2010).…”
Section: Paternal and Maternal Haplogroup Genotyping Of Each Individualsupporting
confidence: 61%
“…Then, we achieved the genotyped data of these samples using the Affymetrix WeGene V1 Array, which includes 492,683 genome-wide SNPs and is referred to as the "500K dataset" elsewhere in this article. Other experimental and bioinformatic procedures for genotyping were consistent with the protocol documented in the previous studies (Huang et al, 2018;.…”
Section: Sampling and Genotypingmentioning
confidence: 99%
“…These datasets included all publicly available ancient DNA data published before 2021 and 2054 individuals from the 1000 Genomes Project, 300 individuals from 142 worldwide populations from Simons Genome Diversity Project, and 928 sequence genomes in the sequenced HGDP. Genotype data obtained using the Affymetrix Human Origins were also included here (42)(43)(44). The used reference populations in the merged 1240K dataset included all publicly available ancient genomes and the sequenced genomes in the HGDP project (45).…”
Section: Reference Population Datasetsmentioning
confidence: 99%